ENTRE FAMÍLIA, TRABALHO E ESPAÇOS PÚBLICOS: A MULHER NAS PÁGINAS DA REVISTA GRAN-FINA (1940-1942) - Santos, Jasmine Aparecida Horst dos (2017)
The woman’s role at society changes as time goes by. Their functions, obligations and subjectivities vary in accordance with historical period. Our work offers a reflection about making female identity included in Gran-fina magazine, a periodic of generalities published on the Curitiba city on beginning of 40’s. The woman is composed of several facets, on fashion proposed by Hall (2004). Therefore, it is interesting to notice how those different identities were represented on the magazine pages and even to be about media that did not circulate for long, it is possible to look that changes happened on these identities and on the way how the journalistic speech used to talk about that. The journalistic speech does not understood here as a place of woman's historic description, but as a place of reaffirmation of meanings that makes possible to understand the historic context and cultural wherein the magazine was inserted and the way how the woman was seen by society from Parana state. Therefore, we will use as a base cultural studies, and identity studies, making use of authors such as Hall and Bauman, and gender, with Scott, Butler and Beauvoir. Our analysis will be based on Hermeneutics, or content analysis.